Information Theoretical Analysis of Biometric Generated Secret Key Sharing Model - Haroutunian. Mariam E.; Narek S. Pahlevanyan (Изд-во НАН РА)
We investigate the biometric generated secret key sharing system. We consider the generalization of the secret key rate, studied by Ignatenko and Willems [1]: the notion of E-achievable secret key rate is introduced. The lower and upper bounds for the largest E-achievable secret key rate are obtained.
Keywords: Mathematics; Computer software